2020
DOI: 10.1038/s41556-020-00578-6
|View full text |Cite
|
Sign up to set email alerts
|

Nucleated transcriptional condensates amplify gene expression

Abstract: Liquid-liquid phase separation is thought to underly gene transcription, through the condensation of the large-scale nucleolus, or in smaller assemblies known as transcriptional hubs or condensates. However, phase separation has not yet been directly linked with transcriptional output, and our biophysical understanding of transcription dynamics is poor. Here, we utilize an optogenetic approach to control condensation of key FET-family transcriptional regulators, particularly TAF15. We show that amino acid sequ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
214
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(235 citation statements)
references
References 60 publications
16
214
5
Order By: Relevance
“…Compartmentalization allows for high local concentrations of biomolecules and their substrates and exclusion of other molecules that are not functionally relevant ( Figure 3A) (Gibson et al, 2019;Li et al, 2020). In addition, condensates are nonstoichiometric assemblies of factors involved in shared processes, so, for example, a condensate at the promoter of a gene can assemble multiple RNA polymerase molecules, thereby producing a burst of transcription (Cho et al, 2018;Guo et al, 2019;Kwon et al, 2013;Sabari et al, 2018;Wei et al, 2020). Condensates can form and dissolve in short time frames, which provides the cell with a means to produce transient compartments, thereby releasing biomolecules for use elsewhere when they are no longer needed at a specific location .…”
Section: Biomolecular Condensatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Compartmentalization allows for high local concentrations of biomolecules and their substrates and exclusion of other molecules that are not functionally relevant ( Figure 3A) (Gibson et al, 2019;Li et al, 2020). In addition, condensates are nonstoichiometric assemblies of factors involved in shared processes, so, for example, a condensate at the promoter of a gene can assemble multiple RNA polymerase molecules, thereby producing a burst of transcription (Cho et al, 2018;Guo et al, 2019;Kwon et al, 2013;Sabari et al, 2018;Wei et al, 2020). Condensates can form and dissolve in short time frames, which provides the cell with a means to produce transient compartments, thereby releasing biomolecules for use elsewhere when they are no longer needed at a specific location .…”
Section: Biomolecular Condensatesmentioning
confidence: 99%
“…Condensates often contain components that can anchor the body to a specific location in the cell. For example, nuclear condensates can form with proteins that bind to specific DNA or RNA sequences, and cytoplasmic condensates can form at sites on the plasma membrane ( Figure 3B) (Boija et al, 2018;Case et al, 2019a;Huang et al, 2019;Shrinivas et al, 2019;Su et al, 2016;Wei et al, 2020). Transcriptional condensates form at specific enhancer and promoter elements by virtue of selective transcription factor (TF) binding (Boija et al, 2018;Shrinivas et al, 2019).…”
Section: Localizationmentioning
confidence: 99%
“…LLPS arises via transient multivalent interactions of intrinsically disordered protein domains, creating an exclusionary local protein-RNA environment (21)(22)(23)(24). The formation of liquid-like protein droplets could have a number of important functional implications to (i) enhance TF binding site occupancy and residence time, (ii) mediate the recruitment of co-activators, (ii) reduce target site search time (25), (iv) contribute to TF target site selection (26) and (v) enhance transcription (27,28). However, alternative mechanisms to phase separation exist for the assembly of transcriptionally active or silenced subcompartments that include classical (cooperative) chromatin binding and formation of well-defined multi-subunit protein complexes (18,(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it has been found that, in proximity to active genes, the PolIIs are incorporated in membrane-less droplets, maintained by liquid-liquid phase separation (LLPS) from the rest of the nucleus, with the net effect of locally increasing the population of factors involved in initiation; when PolII is liberated from this domain, transcription can be initiated [23][24][25][26][27][28]. LLPS also provides an explanation for the hitherto enigmatic action-at-a-distance type of gene regulation by distal enhancers, as the nuclear condensates are indeed able to restructure the genome, albeit results on LLPS are relatively preliminary at this stage [29,30].…”
Section: Introductionmentioning
confidence: 99%